Primer for nutritionists: Managing the side effects of antidepressants. (October 2016) - Tarleton, Emily K.; Kennedy, Amanda G.; Daley, Christopher
Summary: Depression is a chronic disease affecting a significant portion of the U.S. population. Due to the popularity of ADs most nutrition professionals working in the outpatient setting will encounter patients taking one of these medications. Nutritionist can assist patients in managing the short and long term side effects of ADs and, taking into account other nutritional issues, improve overall wellbeing of the patient. The objective of this paper is to identify what side effects nutritionists can help manage, provide the information necessary to help nutritionists feel comfortable assisting with that management, and, as a result, play a valuable role in the team that is vested in the health and wellbeing of the patient.